The Use of Vibrotactile Feedback to Restore Texture Recognition Capabilities, and the Effect of Subject Training - Motamedi, M. Reza; Roberge, Jean-Philippe; Duchaine, Vincent (IEEE transactions on neural systems and rehabilitation engineering, 2017)
This paper presents a vibrotactile haptic feedback system for use under dynamic conditions, verifies its functionality, and shows how results may be affected by the amount of training that subjects receive. We hope that by using vibrotactile feedback to distinguish between different textures, upper-limb amputees may be able to partially regain the sense of touch. During a previous experiment (Motamedi et al., 2015) we noticed a correlation between how familiar the subjects were with haptic systems, and how well they were able to use the haptic system to accurately identify textures. This observation lead us to conduct a second experiment, the results of which are the main focus of this paper. We began with a group of subjects who were completely unfamiliar with haptic systems, and tracked the improvements in their accuracy over a period of four weeks. Although the subjects showed a 16% improvement in their ability to recognize textures, going from a 64% success rate after the first week to 80% after the fourth, perfect accuracy was not attained. A subsequent experiment, however, shows that this result should not diminish our perception of the haptic system's effectiveness. When we asked the same subjects to identify the textures using only their fingertips, we found that even humans cannot distinguish between near-identical textures with complete accuracy. The subjects' overall success rate when using their own hands was 91%, demonstrating that the proposed haptic system is not far from achieving the same texture recognition capabilities as the human sense of touch.